2014
DOI: 10.1590/1807-1929/agriambi.v18nsupps39-s45
|View full text |Cite
|
Sign up to set email alerts
|

Componentes de produção do girassol Embrapa 122-V2000 sob salinidade da água e adubação nitrogenada

Abstract: RESUMO O trabalho foi realizado com objetivo de avaliar os componentes de produção da cultura do girassol, submetida à irrigação com águas salinizadas e adubação nitrogenada. O experimento foi conduzido em ambiente protegido pertencente a Universidade Federal de Campina Grande, durante o período de abril a julho de 2012, em delineamento inteiramente casualizado usando o arranjo fatorial 5 x 5, referente aos níveis de salinidade da água de irrigação, expressas pelas condutividades elétricas: 0,7; 1,7; 2,7; 3,7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
1
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 17 publications
2
1
1
1
Order By: Relevance
“…Nobre et al (2011) observed a linear reduction of the PROD with the increment of the EC of the irrigation water, obtaining 17.4 g/plant when the plants were irrigated with higher levels of EC. Centeno et al (2014) also observed similar results.…”
Section: Resultssupporting
confidence: 74%
“…Nobre et al (2011) observed a linear reduction of the PROD with the increment of the EC of the irrigation water, obtaining 17.4 g/plant when the plants were irrigated with higher levels of EC. Centeno et al (2014) also observed similar results.…”
Section: Resultssupporting
confidence: 74%
“…The reduction of dry phytomass from these ECw levels is closely related to the effects of the accumulation of the concentration of soluble salts, which is a limiting factor to the development of most crops. Thus, this behavior can be understood as a possible adjustment mechanism of the plant to reduce the effects of salinity, because plants undergo morphological and physiological changes such as reduction of biomass, when subjected to salt stress (Centeno et al, 2014). Similar result was reported by Távora et al (2004), who found reduction of dry phytomass in young soursop plants subjected to salt stress.…”
Section: Effect Of Saline Stress and Nitrogen Doses On Phytomass Prodsupporting
confidence: 80%
“…Regarding the Embrapa 122 genotype, although there was no significant effect of irrigation water salinity on production variables in our study, the increase in irrigation water salinity had a negative linear effect on the production of achenes, the number of achenes, viable achenes and a mass of one hundred achenes of this genotype in pot experiments carried out in the same region (Nobre et al 2011;Travassos et al 2011;Centeno et al 2014). Meanwhile, the Multissol genotype was part of fourteen of the Embrapa Soja Sunflower Genotype Evaluation Assays in 12 states from north to south of Brazil and the DF from 2017 to 2018 (Carvalho et al 2018a).…”
Section: Discussioncontrasting
confidence: 64%